Optimizing grid with dynamic line rating of conductors: a comprehensive review - Abas, Nurul Husniyah; Kadir, M.Z.A.A.; Azis, N.; Jasni, J.; Aziz, N.F.A.; Khurshid, Z.M. (IEEE, 2024)
As the world is pledged towards net zero carbon by 2050, the need for clean and efficient energy transitions is more critical than ever. Optimizing the power grid transfer capacity is crucial for maintaining grid stability and reliability. Ageing infrastructure, population growth, and revolutionary technological developments increase the demand for grid modernization and resilience investments. Climate change and natural disasters highlight the need for adaptive load-shedding schemes. The two possible ways to optimize the grid are an ampacity increase or a voltage increase. While increasing voltage provides the most significant rise in rating, it comes with high investment costs. Out of all the options available, dynamic line rating (DLR) is the most efficient and cost-effective solution. This paper provides a comprehensive review of the optimization of the grid transfer capacity using DLR. The review critically examines different line rating methods, the DLR system, factors that need to be considered before DLR implementation, and its advantages and disadvantages. Also, the review presents the real-world applications and case studies, standards and regulations involved, and current approaches and challenges for implementing DLR in Malaysia. Additionally, we highlight the most commonly used standards to calculate the conductor’s ampacity for the steady-state and dynamic state. Moreover, this review work presents how DLR can advance the grid’s flexibility, considering its significance for cleaner energy production in the future, challenges related to wind energy power generation, and their mitigations. This work provides a shortcut path for researchers and utilities to understand DLR and as a reference for future research to advance clean energy in response to changing energy needs and climate conditions.